Persuasive mathematics courseware design model for special need children - Sulaiman, Siti Nur Adilah (2016)
There has been a big growth on number of research of courseware design model for children with special needs. A lot of people interested in this topic. However, there is still lack of courseware design model for children with special needs especially in learning mathematics. Reviews from literatures indicate that content application such as courseware specifically designed to cater for the needs of children with special needs in learning is highly scarce. It is found that most of the existing content applications including courseware have focused on the needs of normal learners, in which most of this courseware means too little to the children with special needs learners with their own problem of learning difficulty. Across many courseware reviewed in this research, only two of them are for learning mathematics. Children with special needs required special module or syllabus that can fit in well with their impairment. Thus, this study aims at studying the core element needed in education courseware for children with special needs. In this study, six courseware components have been proposed; which are Structural Component, Content Composition, Design Guideline, Learning Theory, Learning Approach and Technology. To test the design model, some pre-tests and post-tests, observations and evaluations are conducted. The result of the test shows the improvement in their mathematical skill. In addition, the children have shown positive behaviour change in learning mathematics throughout the testing period. Furthermore, the result has also been acknowledged by expert as a useful learning tool for the children with special needs. In this study, MyMath has been proven to be an effective courseware for learning mathematic among children with special needs.